Investigation of a Nanophotonic Sensor with Electrode Modified by Semiconductor Quantum Dots - O.A. Sushko; M.M. Rozhitskii (Журнал нано- та електронної фізики)
This paper focuses on optical sensors, namely nanophotonic ones intended for liquid media contained polynuclear aromatics assay. Developed by us nanophotonic sensor includes optically transparent working electrode modified by quantum-dimensional structures such as spherical semiconductor quantum dots (QDs). Monomolecular layer of QDs is plotted onto the electrode by Langmuir-Blodgett technology. Particular attention is paid to the processes of assay in nanophotonic sensor. As an analyte we used polycyclic aromatic hydrocarbon (PAH) such as benzo[a]pyrene (BP), which is known for its carcinogenic properties. The developed nanophotonic sensor can be used in ecology for organic carcinogens detection in water objects of environment as well as for biomedical, physical chemical assays and some others.